Ensuring adoption of central bank digital currencies: An easy task or a Gordian knot? - Alejandro Zamora-Pérez; Eliana Coschignano; Lorena Barreiro (European Central Bank (ECB), 2022)
Central banks have been discussing the introduction of a retail central bank digital currency (rCBDC) for some time. However, potential obstacles to its adoption by consumers and retailers remain largely unexplored in the academic and policy literature. This paper surveys the key elements involved in the adoption of any new means of payment and discusses failed and ongoing initiatives with public digital money. It concludes that ensuring the desired level of adoption of rCBDCs may impose significant constraints on central bank design choices and policy goals. In fact, in some settings, central banks may find themselves on the horns of a dilemma in seeking to balance the needs to (i) preserve the central bank's hierarchy of policy goals, (ii) increase the chances of adoption and use of rCBDCs by consumers and retailers, and (iii) avoid any adverse economic effects.
Keywords: E42; E58; D12; 330; central bank digital currency; means of payment; demand for money